Sensitivity of a tonne-scale NEXT detector for neutrinoless double-beta decay searches - Adams, C. (2021)
The Neutrino Experiment with a Xenon TPC (NEXT) searches for the neutrinoless double-beta (0 ) decay of 136Xe using high-pressure xenon gas TPCs with electroluminescent amplification. A scaled-up version of this technology with about 1 tonne of enriched xenon could reach in less than 5 years of operation a sensitivity to the half-life of 0 decay better than 1027 years, improving the current limits by at least one order of magnitude. This prediction is based on a well-understood background model dominated by radiogenic sources. The detector concept presented here represents a first step on a compelling path towards sensitivity to the parameter space defined by the inverted ordering of neutrino masses, and beyond.